5-(9-(p-Tolyl)-2,3,4,4a,9,9a-hexahydro-1H-1,4-methanocarbazol-6-yl)thiophene-2-carbaldehyde - Nikita S. Gudim; Ekaterina A. Knyazeva; Oleg A. Rakitin (Molbank, 2024)
Donor–π spacer–acceptor (D–π–A) dyes are among the most attractive structures for the design of organic dye-sensitized solar cells (DSSCs). Typically, the key intermediates for these sensitizers are D–π compounds containing an aldehyde group to which an anchor acceptor group is attached via the Knoevenagel reaction. In this communication, 5-(9-(p-tolyl)-2,3,4,4a,9,9a-hexahydro-1H-1,4-methanocarbazol-6-yl)thiophene-2-carbaldehyde was prepared via the Suzuki cross-coupling reaction. The structure of the newly synthesized compound was established by means of high-resolution mass spectrometry, 1H NMR, 13C NMR, IR, and UV–Vis spectroscopy. The title compound would be used in the synthesis of sensitizers for DSSCs.